Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s12311-020-01111-z
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Maturation of the Cerebellar White Matter—an Instructive Environment for Cerebellar Inhibitory Interneurons

Abstract: In the developing cerebellum, the nascent white matter (WM) serves as an instructive niche for cerebellar cortical inhibitory interneurons. As their Pax2 expressing precursors transit the emerging WM, their laminar fate is programmed. The source(s) and nature of the signals involved remain unknown. Here, we used immunocytochemistry to follow the cellular maturation of the murine cerebellar WM during this critical period. During the first few days of postnatal development, when most Pax2 expressing cells are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…Most of the c-Fos-positive cells had an overlap with NeuN ( Figure 1—figure supplement 2A ), but not with GAD67 ( Figure 1—figure supplement 2B ). As previously reported ( Groteklaes et al, 2020 ), clear signals of GFAP, a marker of glial cells, were not detected in the DCN, and consequently, cFos-positive cells in the DCN were GFAP negative ( Figure 1—figure supplement 2C ). These results indicate that cells in the DCN activated by RS are glutamatergic neurons.…”
Section: Resultssupporting
confidence: 84%
“…Most of the c-Fos-positive cells had an overlap with NeuN ( Figure 1—figure supplement 2A ), but not with GAD67 ( Figure 1—figure supplement 2B ). As previously reported ( Groteklaes et al, 2020 ), clear signals of GFAP, a marker of glial cells, were not detected in the DCN, and consequently, cFos-positive cells in the DCN were GFAP negative ( Figure 1—figure supplement 2C ). These results indicate that cells in the DCN activated by RS are glutamatergic neurons.…”
Section: Resultssupporting
confidence: 84%
“…Next, we examined the expression of known glial progenitor markers in these putative GPC populations using anti-CNP (2ʹ,3ʹ-cyclic nucleotide 3ʹ-phosphodiesterase) and anti-NG2 antibodies. CNP is expressed during OL development ( Groteklaes et al., 2020 ). In P0, CNP expression was not observed in the developing cortex ( Figure S2 A), and was weakly detected in the corpus callosum of P7 cortex ( Figure S2 B), consistent with a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting our qPCR data, immunohistochemical analysis of Pax2-labelled cerebellar sections revealed that Tsc1 +/cerebella presented with an increased number Pax2 + cells (Figure 4B, C). In addition, these cells were most abundant in the cerebellar white matter (Figure 4B), altogether suggesting the presence of an immature Pax2 phenotype in Tsc1 +/mice (52,53).…”
Section: Overactive Mtor Pathway In P7 Cerebellum Leads To Perturbed Interneuron Development In Tsc1 +/Micementioning
confidence: 93%